ANÁLISE DE APLICABILIDADE DO PRINCÍPIO DA PRECAUÇÃO ÀS INTERAÇÕES SOCIAIS DIGITAIS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
ABSTRACTThis article addresses the constitutional guarantee of the preservation of the environment and health as essential to the quality of life, as established in the Brazilian Constitution of 1988, notably in articles 170, V, 200, and 225, IV and V. It also highlights the role of the State in controlling and regulating goods and services that may pose risks to human health. With the expansion of social interactions in digital environments, current regulation focuses primarily on physical interactions, which raises concerns about the risks of digital interactions to users' health and mental integrity. These digital environments are often controlled by the users or developers themselves, which makes it challenging to fulfill the State's duty to ensure an ecologically balanced environment. This study employed the scientific methodology of the hypothetical-deductive method, supported by a comprehensive literature review, to investigate and analyze the relationships between key variables in our field of research. The article proposes the analysis of the applicability of the precautionary principle of environmental law to mitigate imminent risks to the community in the context of digital interactions, emphasizing the need for public policies and measures to prevent harm related to these risks.Keywords: Collective Law. Health. Cyberculture. Precautionary principle.